1996
DOI: 10.1046/j.1471-4159.1996.66020443.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Cocaine Treatment on μ‐ and δ‐Opioid Receptor mRNA Levels in Dopaminergically Innervated Brain Regions

Abstract: The regulation of μ‐(MOR) and δ‐opioid receptor (DOR) after chronic cocaine administration has been studied. Male Sprague‐Dawley rats were treated for 3 days with saline and cocaine (50 mg/kg/day) delivered by osmotic minipump. Expression of MOR and DOR mRNA in olfactory bulb, nucleus accumbens, and caudate‐putamen (caudal and rostral parts) was estimated using quantitative competitive PCR assays after reverse transcription. No changes in the levels of mRNA for DOR were detected after exposure to cocaine in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…In fact, we have reported that rats maintained on high-dose methadone maintenance show no cocaine-place preference and no cocaine-induced up-regulation of mu-opioid receptor mRNA in the nucleus accumbens core (Leri et al, 2006). This is notable because the effect of cocaine exposure on mu-opioid receptor density and function in mesocorticolimbic areas (Azaryan et al, 1996;Unterwald et al, 1992;Unterwald, 2001;Yuferov et al, 1999) has been associated to the intensity of cocaine cravings in humans (Gorelick et al, 2005;Zubieta et al, 1996), and to a variety of behavioral, electrophysiological and neurochemical responses to cocaine in animals (Mathon et al, 2005a(Mathon et al, , b, 2006Tang et al, 2005;Hummel et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, we have reported that rats maintained on high-dose methadone maintenance show no cocaine-place preference and no cocaine-induced up-regulation of mu-opioid receptor mRNA in the nucleus accumbens core (Leri et al, 2006). This is notable because the effect of cocaine exposure on mu-opioid receptor density and function in mesocorticolimbic areas (Azaryan et al, 1996;Unterwald et al, 1992;Unterwald, 2001;Yuferov et al, 1999) has been associated to the intensity of cocaine cravings in humans (Gorelick et al, 2005;Zubieta et al, 1996), and to a variety of behavioral, electrophysiological and neurochemical responses to cocaine in animals (Mathon et al, 2005a(Mathon et al, , b, 2006Tang et al, 2005;Hummel et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…For example, in rats administered cocaine for 14 days in a "binge" paradigm, MOR binding density increased in several regions containing terminals of the mesocorticolimbic dopaminergic system, including areas of the cingulate cortex, the nucleus accumbens, caudate-putamen, and basolateral amygdala (Unterwald et al, 1992(Unterwald et al, , 1994. A direct molecular effect of acute or 3-day cocaine administration on MOR mRNA levels has also been observed with increases in dopaminergically innervated brain regions reported (Azaryan et al, 1996;Yuferov et al, 1999). A positron emission tomography (PET) study in cocainedependent men also showed increases in MOR binding that were associated with cocaine craving (Zubieta et al, 1996).…”
Section: Selected Identified Genesmentioning
confidence: 97%
“…15 mg/kg three times daily at 1 h intervals for 14 days) has been shown to increase levels of mu and kappa opioid receptors in discrete brain regions of the rat, but does not alter the density of delta opioid receptors (Unterwald et al, 1994). Other investigators have demonstrated similar changes in opioid receptor expression following cocaine (Azaryan et al, 1996;Hammer, 1989;Izenwasser et al, 1996). Although delta opioid receptor densities are unaltered, their function is modulated by cocaine and dopamine D1 receptor activation.…”
Section: Introductionmentioning
confidence: 95%